INCIDENCE AND RISK FACTORS OF RETINOPATHY OF PREMATURITY - DR.A.S.JAGADISH,; DR. NIRANJAN H.S.,; DR. NAVEEN BENAKAPPA, (International Journal of Pharma and Bio Sciences, 2016)
The objective of the study was to find out the incidence of Retinopathy of Prematurity (ROP) in preterm babies < 35 weeks and or low birth weight babies <1750 gm and to identify risk factors which could influence the development of ROP. All babies born in our hospital who were <35 weeks gestation or with birth weight <1750 grams admitted to our NICU during the study period were screened for ROP. Relevant patient data including maternal and neonatal risk factors, problems during NICU stay were recorded. Ophthalmoscopic examination was performed at 3-4 weeks of chronological age or 32 weeks post conceptional age and later based on stage of ROP. Out of the 138 preterm babies (eligible for screening) 100 babies could be registered and completed follow-up. The incidence of ROP in study group was 13%. Out of 13 babies who developed ROP, 6 were in stage – 1, 3 were in stage – 2 and 2 were in stage – 3 and 2 in stage 3 with plus disease. On univariate analysis of risk factors lower gestational age, lower birth weight, exposure to oxygen, RDS, hyperoxia>100mmHg, hypoxia <40mmHg, apnea, sepsis, PDA, shock anemia, IVH, ventilation were statistically significant. The incidence of ROP among babies with gestational age <35 weeks or birth weight <1750 gms was 13%. The main risk factors associated with ROP are lower gestational age, lower birth weight, exposure to oxygen, RDS, hyperoxia (>100 mmHg), hypoxia(<40mmHg), apnea, sepsis, PDA, shock, anemia, IVH, ventilation as noted on univariate analysis of risk factors from this study